Cross-border food remittances and mobile transfers: The experiences of Zimbabwean migrants in Cape Town, South Africa - Sithole, Sean (2023)
Mobile transfers have become a defining feature of cross-border remittance transmission in Sub-Saharan Africa (SSA). However, recent studies on mobile transfers have mainly focused on cash remittances and need to pay more attention to mobile food transfers. This paper addresses this research gap on mobile food transfers by examining cross-border food remittances and mobile transfers by Zimbabwean migrants residing in Cape Town, South Africa, to their families and friends back home. In this paper, we seek to understand the factors influencing the uptake of digital food remittances by Zimbabwean migrants who have lived in South Africa for at least three years. The paper is based on a mixed research study carried out in Cape Town during the nationwide COVID-19 lockdown in 2020. The mixed-methods study involved a questionnaire survey of 100 Zimbabwean nationals that was complemented by in-depth interviews with 10 participants selected from the interviewed group. The study findings reveal that the national COVID-19 pandemic lockdown disrupted informal food-remitting channels and, at the same time, helped to solidify the digital and mobile food transfers across national borders that have emerged in SSA in recent years.